PENGARUH DIMENSI DESAIN TERHADAP BOOKING INTENTION PADA BOUTIQUE HOTEL KOTA BANDUNG OLEH GENERASI MILENIAL - Rizky Ramadhan, - (2020)
The purpose of this study was to examine the effect of the design dimensions applied by hotels on the intention to place orders by millennials. Due to the development and growth of boutique hotels which are very numerous in number, so the need to understand the characteristics or patterns of large market segmentation in the future soon in shaping their intentions. Data was collected from the results of distributing Google forms with purposive sampling techniques to millennial generation in Indonesia and having a travel plan in the city of Bandung, and 200 data were used. The findings in this study are that the intention to place a millennial order is only influenced by good design in functionality with fully mediated by emotional arousal. So that the emotional arousal role becomes very important in shaping the intention to place orders from millennial. This finding could have implications for marketing strategies and improvements in the application of hotel room design to influence the intentions of millennial guests.